Review of the Heteroptera (Hemiptera) fauna of Turkey: perspectives for future research - Çerçi, Barış; Koçak, Özgür; Tezcan, Serdar (European Journal of Taxonomy, 2024)
Research on the Heteroptera fauna of Turkey has not been extensive enough to illustrate its true diversity. Although several factors contribute to this, the lack of an up-to-date and comprehensive review is a basic factor. To address this issue, we compiled a list of all the Heteroptera species recorded from Turkey in the literature and iNaturalist. In addition, we re-examined several specimens preserved in the Lodos Entomological Museum, İzmir, Turkey (LEMT). Consequently, we excluded 24 species from the checklist of Heteroptera fauna of Turkey, and proposed a new synonymy: Psallus (Psallus) pardalis Seidenstücker, 1966 = Psallus (Psallus) oenderi Wagner, 1976 syn. nov. Furthermore, we recorded following six species from Turkey for the first time: Blissus hirtulus Burmeister, 1835 (Blissidae), Loricula (Loricula) pselaphiformis Curtis, 1833 (Microphysidae), Globiceps (Globiceps) coryli V.G. Putshkov, 1970, Heterocordylus (Heterocordylus) cytisi Josifov, 1958, Mesopsallus fagi (Drapolyuk, 1990) and Psallus (Psallus) helenae Josifov, 1969 (Miridae); and described following six species as new for science: Orthonotus efei Çerçi & Koçak sp. nov., Orthotylus (Parapachylops) oenderi Çerçi, Tezcan & Koçak sp. nov., Orthotylus (Pinocapsus) girayi Çerçi & Tezcan sp. nov., Psallus (Psallus) eceae Çerçi & Koçak sp. nov., Psallus (Psallus) pehlivani Çerçi & Tezcan sp. nov. and Ribautocapsus tezcani Çerçi sp. nov. Altogether, 1668 species of Heteroptera have been recorded from Turkey (664 species in the European part and 1633 species in the Anatolian part) until now, out of them, the presence of 37 species needs confirmation. We determined the chorotypical composition of species as follows: Mediterranean (399 spp., 23.9%), European (380 spp., 22.8%), Local (280 spp., 16.8%), Widespread (182 spp., 10.9%), Endemic (128 spp., 7.7%), Turanian (127 spp., 7.5%), Turano-Mediterranean (89 spp., 5.3%), Europeo-Mediterranean (68 spp., 4.1%) and Alien (12 spp., 0.7%). We showed that provinces in the Eastern Anatolian, Southeastern Anatolian, and Black Sea regions had lower numbers of species recorded, compared to the provinces in the remaining regions. Finally, we underlined that 109 species, absent from Turkey, were recorded from three or more neighboring countries of Turkey. In summary, our findings emphasize that despite the abundant research devoted over the last 150 years to the Heteroptera fauna of Turkey, our understanding of it remains incomplete in the majority, if not in all, of the regions. Our findings strongly encourage further research, particularly in regions with small numbers of recorded species. This endeavor will undoubtedly lead to numerous novel discoveries and provide a better understanding of the true Heteroptera diversity in Turkey.